RETRACTED: Linc00662 Promotes Tumorigenesis and Progression by Regulating miR-497-5p/AVL9 Axis in Colorectal Cancer - Wang, Huaiming; Yu, Mengya; Hu, Weixian; Chen, Xin; Luo, Yuwen; Lin, Xiaosheng; Zeng, Yongming; Yao, Xueqing (Frontiers in Genetics, 2020)
Background: Recently, multiple lines of evidence have demonstrated that linc00662 serves as an oncogene in various cancers. However, the exact mechanism of oncogenesis mediated by linc00662 in colorectal cancer (CRC) remains unknown. In this study, we aimed to explore the biological role of linc00662 in the regulation of CRC progression. Methods: Both gene expression omnibus (GEO) and the cancer genome atlas (TCGA) datasets were used to evaluate the expression of linc00662. RT-qPCR was used to analyze the expression of linc00662, miR-497-5p, and AVL9 in CRC clinical samples and cell lines. Cell Counting Kit-8 (CCK-8), flow cytometry, transwell assay, and xenograft model were used to investigate the effect of linc00662 on CRC cell proliferation, cell cycle, and metastasis. Western blot analysis was used to analyze the expression of the epithelial-mesenchymal transition (EMT)-associated markers. Furthermore, bioinformatics analysis and mechanism assays were used to elucidate the underlying mechanism. Dual-luciferase reporter assays were used to analyze the regulatory relationships among linc00662, miR-497-5p, and AVL9. Results: In this study, we found that the expression of linc00662 was significantly upregulated in CRC tissues compared to normal tissues and positively correlated with tissue differentiation, T stage, and lymphatic metastasis. Further, our data showed that the expression of linc00662 was positively associated with lymph node metastasis, TMN stage, and poor-moderate differentiation. Patients with higher linc00662 expression level were more likely to have poorer overall survival. Knockdown of linc00662 inhibited CRC cell growth, induced cell apoptosis, triggered cell cycle arrest at G2/M phase, and suppressed cell migration and invasion through regulating the EMT pathway. Further, mechanistic studies revealed that knockdown of linc00662 significantly reduced the expression of AVL9, a direct target of miR-497-5p. Conclusions: Linc00662 was significantly upregulated in CRC, and mediated CRC progression and metastasis by competing with miR-497-5p to modulate the expression of AVL9. Therefore, our result sheds light on the potential application of linc00662 in CRC diagnosis and therapy.